Sustainable digital leap: a bibliometric study on its impact on human learning and organizational development in the MENA region - Ajay Singh (Future Business Journal)
Abstract The study aims to explore how sustainable digital transformation affects human learning and organizational development in MENA region using bibliometric analysis. The researchers used Scopus and WOS databases for data extraction. The researcher analyzed the cumulative data using performance analysis, and scientific mapping with VOS Viewer software. The findings indicated that Blau, I from Israel is the leading author, King Faisal University from Saudi Arabia is the most productive institution, “International Journal of Emerging Technologies in Learning” is the most productive journal, and “Investigating users’ perspectives on e-learning: An integration of TAM and IS success” is the highly cited article in target domain. Furthermore, the scientific mapping indicated that Saudi Arabia has highest co-author country collaboration. Finally, E-learning is the high co-occurred keyword because of collaborative research from MENA region for the subject. The study provides most productive author, institutions, journal, articles, country, and keyword in order to understand the literature for the impact of sustainable digital transformation on human learning and organizational development from MENA region.